A homozygous mutation of GNRHR in a familial case diagnosed with polycystic ovary syndrome. Issue 5 (May 2017) - Caburet, Sandrine; Fruchter, Ronit Beck; Legois, Bérangère; Fellous, Marc; Shalev, Stavit; Veitia, Reiner A
Abstract : Context: PCOS is a heterogeneous condition characterized by hyperandrogenism and chronic anovulation and affects about 10% of women. Its etiology is poorly known, but a dysregulation of gonadotropin secretion is one of its hallmarks. Objective: As the etiology of PCOS is unclear, we have performed a genome-wide analysis of a consanguineous family with three sisters diagnosed with PCOS. Methods: Whole-exome sequencing and Sanger sequencing confirmation. Results: Whole-exome sequencing allowed the detection of the missense variant rs104893836 located in the first coding exon of the GNRHR gene and leading to the p.Gln106Arg (p.Q106R) substitution. Sanger sequencing of all available individuals of the family confirmed that the variant was homozygous in the three affected sisters and heterozygous in both parents. Conclusions: This is the first description of a GNRHR gene mutation in patients diagnosed with PCOS. Although we do not exclude a possible interaction of the identified variant with the genetic background and/or the environment, our result suggests that genetic alterations in the hypothalamo–pituitary axis may play role in the pathogenesis of PCOS.